Inequality and the Structure of Countries' External Liabilities - Harms, Philipp (IMF Working Papers; Working Paper ;, 2022)
In this paper, we present empirical evidence that higher income inequality is associated with a greater equity share in countries' external liabilities, and we develop a theoretical model that can explain this observation: In a small open economy with traded and nontraded goods, entry barriers depress entrepreneurial activity in nontraded industries and raise income inequality. The small number of domestic nontraded-goods firms leaves room for foreign firms to operate on the domestic market, and it reduces external borrowing. The model suggests that barriers to entrepreneurial activity could be conducive to attract equity-type capital inows. Our empirical results lend some support to this conjecture.